Effect of botanical and physicochemical composition of Argentinean honeys on the inhibitory action against food pathogens - Ramos, Ornella Yolanda; Salomon, Virginia María; Libonatti, Carina; Cepeda, Rosana; Maldonado, Luis Maria; Basualdo, Marina (2018)
Honey is a natural food with functional properties such as antioxidant and antimicrobial activities. These properties vary greatly depending on floral source, climate, and environmental and processing conditions. In this work, we characterized honeys on the basis of their botanical composition and clustered them according to their physicochemical parameters in order to find similarities, and assess their antibacterial action against microorganisms isolated from contaminated food. All honeys studied complied with international quality standards. The data showed differences between multifloral and unifloral honeys in their physicochemical parameters, as well as a direct correlation between colour, phenolic compounds, and antioxidant activity. -Antimicrobial activity resulted from hydrogen peroxide effect. Multifloral honeys with similar phenolic compounds and a botanical composition of eucalyptus and blueweed had greater inhibitory power against E. coli, P. aeruginosa, Salmonella spp., S. aureus and B. cereus.